"Be the change you want to see": A three-part semester-long assignment in an interracial communication class. Issue 4 (2nd October 2018) - Alexander, Alicia; Liu, Min
ABSTRACT: Courses: This three-part semester-long assignment was designed for an undergraduate course in interracial communication. While interracial communication is the primary focus of this assignment, it could easily be adapted to a variety of courses focused on diversity with the goals of improving communication and connectedness among members of other social and cultural groups. Objectives: The interracial communication course seeks to promote a better understanding of, and sensitivity to, the communication dynamics of interracial interactions.